Fontes de carbono de baixo custo para a produção de xilanase termoestável por aspergillus niger - Benedetti, Ana Cláudia Elias Pião [UNESP]; da Costa, Eliana Dantas [UNESP]; Aragon, Caio Casale [UNESP]; dos Santos, Andréa Francisco [UNESP]; Goulart, Antônio José [UNESP]; Attili-Angelis, Derlene [UNESP]; Monti, Rubens [UNESP] (My University, 2013)
A strain of the flamentous fungus Aspergillus niger was isolated and shown to possess extracellular xylanolytic activity. These enzymes have biotechnological potential and can be employed in various industries. This fungus produced its highest xylanase activity in a medium made up of 0.1% CaCO3, 0.5% NaCl, 0.1% NH4Cl, 0.5% corn steep liquor and 1% carbon source, at pH 8.0. A low-cost hemicellulose residue (powdered corncob) proved to be an excellent inducer of the A. niger xylanolytic complex. Filtration of the crude culture medium with suspended kaolin was ideal for to clarify the extract and led to partial purifcation of the xylanolytic activity. The apparent molecular mass of the xylanase was about 32.3 kDa. Maximum enzyme activity occurred at pH 5.0 and 55-60oC. Apparent Km was 10.41 ± 0.282 mg/mL and Vmax was 3.32 ± 0.053 U/mg protein, with birchwood xylan as the substrate. Activation energy was 4.55 kcal/mol and half-life of the crude enzyme at 60oC was 30 minutes. Addition of 2% glucose to the culture medium supplemented with xylan repressed xylanase production, but in the presence of xylose the enzyme production was not affected.

Fontes de carbono de baixo custo para a produção de xilanase termoestável por Aspergillus niger Uma linhagem do fungo filamentoso Aspergillus niger foi isolada e apresentou atividade xilanolítica extracelular. Estas enzimas possuem grande potencial biotecnológico e podem ser aplicadas em diversas indústrias. O fungo produziu sua maior atividade de xilanase em um meio contendo CaCO 3 0,1%, NaCl 0,5%, NH 4 Cl 0,1%, 0,5% água de maceração de milho e 1% de fonte de carbono, em pH 8,0. Um resíduo lignocelulósico de baixo custo (sabugo de milho em pó) mostrou ser um excelente indutor do complexo xilanolítico em A. niger . A filtração do extrato cru com caulim foi ideal para a clarificação do extrato e levou à purificação parcial da enzima. A massa molecular aparente da xilanase foi de 32,3 kDa. A máxima atividade da enzima ocorreu em pH 5,0 e a 55-60ºC. O K m aparente foi de 10,41 ± 0,282 mg/mL e a V max foi de 3,32 ± 0,053 U/mg proteína, utilizando-se xilana birchwood como substrato. A energia de ativação foi de 4,55 kcal/mol, e a meia-vida da enzima a 60ºC foi de 30 minutos. A adição de 2% de glicose ao meio de cultura suplementado com xilana reprimiu a produção de xilanase, mas em presença de xilose a produção da enzima não foi afetada.
Low-cost carbon sources for the production of a thermostable xylanase by Aspergillus niger
Keywords: Agroindustrial residues; Aspergillus niger; Thermostability; Xylanolytic enzymes; bagasse; kaolin; unclassified drug; xylan; xylan 1, 4 beta xylosidase; xylan endo 1, 3 beta xylosidase; animal cell; Aspergillus versicolor; carbon source; chromatography; enzyme synthesis; fungal cell culture; hydrolysis kinetics; kinetics; nonhuman; pH; polyacrylamide gel electrophoresis; protein content; protein determination; temperature; thin layer chromatography; wheat bran